2013
DOI: 10.1007/s11481-013-9514-0
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Tetramethylpyrazine Bis-nitrone (TN-2) Protects Against MPTP/MPP+-Induced Neurotoxicity via Inhibition of Mitochondrial-Dependent Apoptosis

Abstract: Mitochondrial-dependent apoptosis plays an important role in the degeneration of dopaminergic neurons in Parkinson's disease (PD). Methyl-4-phenyl-1,2,3,6-tetra- hydropyridine (MPTP), the most widely used neurotoxin to simulate PD, is converted to 1-methyl-4-phenylpyridinium (MPP(+)) in vivo. MPP(+) induces excessive intracellular reactive oxygen species (ROS), leading to mitochondrial-dependent apoptosis via sequentially opening mitochondria permeability transition pore (mPTP) to release cytochrome c from mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…1b). TN-2 was armed with two powerful free radical-scavenging nitrone moieties and showed remarkable activity protecting neuronal cells from oxidative injury in vitro (Xu et al 2014a) and ischemic stroke injury (Sun et al 2012) and also neurodegenerative diseases in animal models (Xu et al 2014c).…”
Section: Discussionmentioning
confidence: 99%
“…1b). TN-2 was armed with two powerful free radical-scavenging nitrone moieties and showed remarkable activity protecting neuronal cells from oxidative injury in vitro (Xu et al 2014a) and ischemic stroke injury (Sun et al 2012) and also neurodegenerative diseases in animal models (Xu et al 2014c).…”
Section: Discussionmentioning
confidence: 99%
“…We purchased LPS from Sigma-Aldrich Co (St. Louis, MO). The choice of TN-2 concentrations was based on previous studies [16][17][18][19] and the present study of MTT assay.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have showed that TN-2 protected neuronal cells from 6-OHDA-or MPTP/MPP ? -induced neurotoxicity and NF-jB-mediated neuro-inflammation [16][17][18][19]. Despite evidence indicating the neuroprotective effect of TN-2, there is a lack of data describing the role of TN-2 in intrarenal inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Brain tissue fixation, paraffin embedding, sectioning and immunohistochemistry with antibody against TH were performed as described in our previous publications [21,22]. The results were analyzed by counting the numbers of TH-positive cells at ×10 magnifications on a stereomicroscope (BX51, Olympus Corp., Japan).…”
Section: Tissue Processing and Tyrosine Hydroxylase (Th) Immunohistocmentioning
confidence: 99%